Nanocompósitos de borracha natural com celulose II e montmorilonita - Mariano, Roberta Magalhães. (UFRJ, 2011)
[PT]Nesta Tese foram desenvolvidos nanocompósitos por co-precipitação de solução aquosa da montmorilonita sódica (MMT) com látex de borracha natural (NR) e xantato de celulose. Os materiais obtidos foram estudados quanto as propriedades físicas, mecânicas, térmicas, morfológicas, dinâmico-mecânicas e reológicas, que permitiram a realização do estudo das interações carga-matriz e carga-carga.A co-precipitação do xantanto de celulose leva a formação de celulose II (CEL), que foi mantida constante em 15 phr em NR, na avaliação da incorporação de MMT de 0 a 5 phr.A adição da montmorilonita como carga no sistema NR/CEL promoveu melhor desempenho das propriedades mecânicas e dinâmico-mecânicas, identificando o teor máximo de MMT, corroborado pelos resultados de difratometria de raios-X para formação de estruturas lamelares intercaladas e esfoliadas. Através da análise morfológica foi possível identificar a formação dos nanocompósitos e a intercalação e esfoliação do argilomineral na matriz elastomérica juntamente com a celulose. As interações carca-carga e polímero-carga formadas foram caracterizadas através do Efeito Payne e Efeito Mullins, respectivamente.Com estas caracterizações o teor de 3 phr foi identificado como o melhor conteúdo de MMT presente na goma pura e no sistema NR/CEL. A técnica de co-coagulação utilizada nesta Tese mostrou-se efetiva na obtenção dos nanocompósitos de borracha natural com celulose e montmorilonita, podendo ser aplicada a nível industrial.[EN]In this Thesis nanocomposites were developed by co-precipitation of aqueous solution of sodium montmorillonite (MMT) with natural rubber latex and cellulose xanthate. The materials obtained were studied as for mechanical, thermal, morphological, dynamic-mechanical and rheological properties, which allowed the investigation on the filler-matrix and filler-filler interactions. The co-precipitation of cellulose xanthate leads to the formation of cellulose II (CEL) which, in the evaluation of MMT ranging from 0 to 5phr, was kept constant, at the level of 15phr, in the NR compounds. The addition of montmorillonite as filler in the NR/CEL system promoted better performance as far as mechanical and dynamic-mechanical properties are concerned, as well as the identification of the maximum allowed level of MMT, corroborated by the results of X ray diffractometry for the formation of lamellar and intercalated structures. From the morphological analysis the identification of nanocomposites formation was possible as well as the intercalation and exfoliation of the argilomineral in the elastomeric matrix together with cellulose. The co-coagulation technique used in this Thesis was found to be effective for the preparation of natural rubber with cellulose and montmorillonite nanocomposites, being applicable at the industrial level. From the morphological analysis the identification of nanocomposites formation was possible as well as the intercalation and exfoliation of the argilomineral in the elastomeric matrix together with cellulose.The interactions filler-filler and polymer-filler formed were characterized by Payne Effect and Mullins Effect, respectively, and the content of 3 phr was identified as the best content of MMT present in neat gum and in the NR/CEL system. The co-coagulation technique used in this Thesis was found to be effective for the preparation of natural rubber with cellulose and montmorillonite nanocomposites, being applicable at the industrial level.